Serum ferritin level and B12 in a sample of Iraqi re-current aphthous stomatitis patients - Ali, Noor S (Journal of Baghdad College of Dentistry, 2022)
Background: Recurrent aphthous stomatitis (RAS) is one of the most common oral mucosal disorders with a prevalence of 50-66%. The prevalence of hematinic deficiencies including ferritin and vitamin B12 deficiencies and their role in the prophylaxis and development of RAS is not well known. Many studies have demonstrated a high prevalence of hematinic deficiencies in patients with RAS. This study aimed to compare the serum level of ferritin and vitamin B12 in patients with recurrent aphthous ulcers and healthy controls. Subjects, Materials and Methods: The data were collected from patients who needed blood analysis to exclude anemia from November 2020 to May 2021. The study was approved by the institutional ethics committee. After recording patients' demographics ( age, gender, occupation, address)  5ml of blood was drawn from patients and controls in educational laboratories centrifuged at 3000 rpm for 10 minutes, then serum was stored at -20°C till the time of assessment of both serum ferritin and vitamin B12. The data were expressed as Mean ± SD. Students Unpaired t-test was used for comparing biochemical parameters between patients and controls and a p-value of